2016
DOI: 10.1016/j.bbi.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high fat diet exposure is associated with increased hepcidin levels, decreased myelination, and neurobehavioral changes in male offspring

Abstract: Maternal obesity induces chronic inflammatory responses that impact the fetus/neonate during the perinatal period. Inflammation, iron regulation, and myelination are closely interconnected and disruptions in these processes may have deleterious effects on neurodevelopment. Hepcidin levels are increased in response to inflammation causing subsequent decreases in ferroportin and available iron needed for myelination. Our current studies were designed to test the hypotheses that: 1) maternal high fat diet (HFD) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 45 publications
4
68
2
Order By: Relevance
“…This effect was also observed in offspring exposed to a high fat diet throughout both the pre- and postnatal period, who showed decreased retention times, higher escape latencies, and less time spent in the target quadrant of the water maze, suggesting impaired spatial memory performance [22,24,25,26]. Similarly contradictory findings have been described using the novel object recognition task, with one experiment reporting decreased exploration of the novel object in young adult male—but not female—offspring of obese dams [44] and another reporting higher initial novel exploration by male offspring exposed to a cafeteria diet during lactation [21]. Again, these discrepancies may relate to the timing of dietary exposure, sex, and age of offspring at testing.…”
Section: Cognitive Function and Mental Health In Offspring Born Tomentioning
confidence: 99%
“…This effect was also observed in offspring exposed to a high fat diet throughout both the pre- and postnatal period, who showed decreased retention times, higher escape latencies, and less time spent in the target quadrant of the water maze, suggesting impaired spatial memory performance [22,24,25,26]. Similarly contradictory findings have been described using the novel object recognition task, with one experiment reporting decreased exploration of the novel object in young adult male—but not female—offspring of obese dams [44] and another reporting higher initial novel exploration by male offspring exposed to a cafeteria diet during lactation [21]. Again, these discrepancies may relate to the timing of dietary exposure, sex, and age of offspring at testing.…”
Section: Cognitive Function and Mental Health In Offspring Born Tomentioning
confidence: 99%
“…Similarly to hyperoxia, maternal obesity and neonatal HI increase cytokine levels in the offsprings' brain. This was demonstrated in rodent and non-human primate models of obesity 34,154,155 . Moreover, after neonatal hypoxic-ischaemic brain injury in rodents, cerebral levels pro-inflammatory proteins (e.g.…”
Section: Cytokinesmentioning
confidence: 85%
“…In our study some parameters of physical and neurobehavioral development were delayed in both male and female offspring. Birth through 21 days is a time of active brain growth, extension of neuronal processes, migrating oligodendrocytes and myelination (Graf et al, 2016). Possibly, the deficit in neurobehavioral reflex ontogeny should be associated with delayed myelination since previous studies have shown that maternal high fat diet prior to and during pregnancy is associated with decreased myelination in some brain regions (Graf et al, 2016).…”
Section: Discussionmentioning
confidence: 99%